Design and Implementation of an Upper Limb Prosthetic Hand Using a Pressure Sensor - Al-Khazzar, Ahmed M.; Hussain, Jabbar S.; Raheema, Mithaq Nama (Basrah Journal for Engineering Sciences, 2024)
Smart prostheses hands have seen vast advancement in recent years. Amputees with upper hand loss have better access to intelligent prostheses that help them with their daily life activities. Smart prostheses however are still in development and have a few disadvantages, such as being expensive, complex, require training and being error prone in some cases. In this paper a simple, cost effective, practical upper limb prosthetic device is proposed that uses pressure sensors to acquire the action intent from the amputees. The pressure sensor serves as input signal to the Control Unit (CU). Using a selector keyboard, the amputee can choose between five predefined movements. The advantages of the proposed system compared to other prostheses using EMG, EEG, Voice is design simplicity and cost. The approximate cost of the proposed prosthetic hand is less than 200$. In addition, some of the complexities and error prone properties of the other alternatives are avoided and less probability of use fatigue is achieved.